Factors Affecting the Incidence of Anemia in Pregnant Women - Dina Mei Saputri; Lisa Trina Arlym; Rini Kundaryanti (Indonesian Journal of Global Health Research, 2026)
Iron deficiency anemia accounts for approximately 75% of all anemia cases and can lead to complications such as fatigue, decreased cognitive function, preeclampsia, low birth weight, and preterm birth. Although the government has provided iron (Fe) tablets, compliance and nutritional adequacy remain major challenges. This study aims to analyze the factors influencing the incidence of anemia among pregnant women at Baamang I Public Health Center in Sampit. This research employed a quantitative approach with a cross-sectional design involving 70 pregnant women selected through consecutive sampling. Data were collected using questionnaires and observations. Information on hemoglobin levels, anemia status, and Fe tablet consumption was obtained through interviews and medical records at a single point in time, consistent with the cross-sectional design. Data were analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses. Among the 70 respondents, 42.9% of pregnant women were diagnosed with anemia. Factors influencing anemia included Fe tablet consumption with a p-value < 0.05. Multivariate analysis revealed that compliance with Fe tablet consumption was the most dominant factor, with an odds ratio (OR) value of 0.000. Maternal age, nutritional status, and compliance with Fe tablet consumption significantly affect the incidence of anemia among pregnant women.